Rancang Bangun Aplikasi Kasir untuk BUMDES Berbasis Web Menggunakan Metode Extreme Programing - Yudi, Yudi; Tedyyana, Agus (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In the digital era, Village-Owned Enterprises (BUMDes) face challenges in managing transactions and stock items that are still done manually using Microsoft Excel. This method is less efficient, prone to errors, and time consuming in data processing. To overcome these problems, this research designs and develops a web-based cashier application using the Extreme Programming method. This method was chosen because of its flexible approach in handling changing user needs and improving the efficiency of software development. This application has main features such as recording transactions, managing stock items, and real-time sales reporting. Testing is done using the Black Box Testing method to ensure that the system runs according to its function. The implementation results show that this application can improve efficiency in recording transactions, reduce errors in data processing, and provide stock information and sales reports more accurately and quickly.